Pilot study on the effect of Yasiin recitation on the haemodynamics of ventilated patients - Sharifudin, Mohd Ariff; Taib, Mai Nurul Ashikin; Razali, Maryamjameelah; Johari, Bushra; Wan Ahmad, Wan Azman (Faculty of Medicine, International Islamic University Malaysia, 2013)
Introduction: Qur’anic verses recitations to ill patients are practiced by many Muslims as a form of healing and worship. The effectiveness has been observed in many medical institutions; however, it has never been objectively measured and documented. This pilot study was conducted to construct a methodological approach to evaluate the therapeutic effects of Yasiin recitation on the haemodynamics of critically ill patients. Methods: Ventilated Muslim patients in coronary care unit of a teaching hospital were evaluated. Yasiin was recited twice; by one of the researchers and then by the patients’ relatives. Mean arterial blood pressure, pulse rate, oxygen saturation level and electrocardiographic changes, were observed. The difference of the parameters before and during recitation was analysed. Results: Five patients fulfilling the selection criteria were selected; two acute myocardial infarctions, two congestive cardiac failures, and a third-degree atrioventricular block. Based on a non-parametric two-related-sample test, the haemodynamic parameters were not significantly affected by Yaasiin recitation. At the end of the study, two of the patients passed away, one patient was extubated and survived. Two patients were still on ventilators when the study had been completed. Limitations in the study were observed and highlighted in explaining the equivocal results. Conclusions: The effect of Yasiin recitation on heamodynamics of patients was not proven in this study. Further refinements might be needed based upon the observation on limitations encountered. It is hoped that this humble effort would pave the way for further studies to explore this field.